The effect of lower extremity masses and volumes on the balance performance of athletes - Akil, M.; Celenk, C.; Burak Aktug, Z.; Marangoz, I.; Ylmaz, T.; Top, E. (Biomedical Research, 2016)
Our study aims to investigate the effects of lower extremity mass and volume characteristics of elite athletes on the balance performances. The study has included 42 elite athletes totally with an average age of 23.45 ± 2.50 years, average height of 173.64 ± 6.96 cm, average weight of 79.55 ± 14.19 kg and average body mass index of 26.22 ± 3.06. The calf, femur, foot and leg volumes of the subjects included in the study have been determined by means of Frustum method however, calf, femur, foot and leg masses of the subjects have been determined by means of Hanavan method. The static and dynamic balance performance of athletes has been measured by Biodex Balance System. Dynamic balance performance has been detected in the levels of 2, 4 and 8. When dynamic balance performances have been evaluated, it has been found that there is a significant difference in low-level balance test (p>0.05), and a positive difference has been found between the masses and volumes of calf (r=0.437), femur (r=0.609), foot (r=0.344) and leg (r=0.607) in terms of good and moderate level of balance performances (p<0.05). According to the results obtained, the masses and volumes of calf, femur, foot and leg of the athletes have affected the balance performances and, as the difficulty level of the balance performance increases, the lower extremity mass and volumes affect the balance performance much more. In conclusion, it has been found that lower extremity masses and volumes affect the balance performance of the athletes positively, and lower extremity mass and volumes are required to be improved enough in the branches that put an emphasis on balance.